Política pública de salud a través del seguro popular: análisis de los "gastos de bolsillo" de las personas atendidas en Morelia, Michoacán - Ramírez Cendejas, Claudia María (Universidad Michoacana de San Nicolás de Hidalgo, 2016)
From reform to the General Health Law in 2003 by which the system of social protection in health is created, Mexico went from investing in health 4.9% that invested in 2000 to 6.2% of its domestic product gross (GDP) in 2013, although we are still below the average of the countries of Latin america that is 7% and the Organization for Economic Co-operation and Development (OECD), which is 8.9%. The great achievement of this reform was to be guaranteed in Article 4 of the Constitution of our country the fundamental right to social protection in health regardless of employment status or social or economic status of people. Seguro Popular (SP) reached full coverage in 2012 with more than 52 million people affiliated, with funding from the popular insurance, hospital infrastructure grew, health centers and care units were strengthened, although we continue with a system fractionated health in various institutions. It is anticipated that more pressure will have on the health system, because the disease has evolved from acute infectious diseases to chronic diseases and being relatively inexpensive to be high-cost diseases diseases, so you should change the paradigm of attention to prevention. That same pressure will be reflected in the pockets of the people to the extent that fails to have an integrated and efficient health system that gives real access to quality health and equity. Although reduced expenses pocket health is evidence that families continue to have a high pocket expenses, either by the shortage in medicines, by the remoteness of health institutions or lack of efficiency in care in medical units and hospitals, among others.

A partir de la reforma a la Ley General de Salud en el año 2003 mediante la cual se crea el régimen de protección social en salud, México pasó de invertir en salud del 4.9% que invertía en el año 2000 a 6.2% de su Producto Interno Bruto (PIB) en el 2013, aunque todavía estamos por debajo de la media de los países de américa latina que es del 7% y de la Organización para la Cooperación y el Desarrollo Económicos (OCDE) que es de 8.9%. El gran logro de esa reforma fue el haber garantizado en el artículo 4° de la Constitución Política de nuestro País el derecho fundamental a la protección social en salud con independencia de la condición laboral o del estatus social o económico de las personas. El Seguro Popular (SP) alcanzó la cobertura total en el año 2012 con más de 52 millones de personas afiliadas, gracias al financiamiento del seguro popular, la infraestructura hospitalaria creció, se fortalecieron centros de salud y unidades de atención, aunque seguimos con un sistema de salud fraccionado en varias instituciones. Se prevé que se tendrá cada vez más presión en el sistema de salud, pues las enfermedades han evolucionado de ser enfermedades infecciosas agudas a enfermedades crónicas y de ser enfermedades relativamente baratas a ser enfermedades de alto costo, por lo que se debe cambiar el paradigma de atención a la prevención. Esa misma presión se verá reflejada en los bolsillos de las personas en la medida que no se logre tener un sistema de salud integrado y eficiente que dé un verdadero acceso a la salud con calidad y equidad.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Políticas Públicas
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2016-1100; Sistema de salud; Política pública de salud; Seguro popular; Gasto de bolsillo; Seguridad social; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1033